Trajectory of Water- and Fat-Soluble Dyes in the Grass-Cutting ant Atta capiguara (Hymenoptera, Formicidae): Evaluation of Infrabuccal Cavity, Post-Pharyngeal Glands and Gaster - Forti, Luiz Carlos [UNESP]; Silva, Marcilio de Souza [UNESP]; Fujihara, Ricardo Toshio [UNESP]; Caldato, Nadia [UNESP]; Garcia, Marise Grecca [UNESP] (California State University, 2012)
The diet of leaf-cutting ants is based on cultivation of their symbiotic fungus, whose successful cultivation depends on the task of incorporation and handling of vegetable substrate. This task may cause the workers to be contaminated with toxic substances and thus decrease the survival of the colony. The objective of this study was to analyze the contamination of workers of Atta capiguara as well as the dissemination trajectory of water- and fat-soluble substances. Four colonies received non-toxic baits containing water-soluble dye Rhodamine-B and three, non-toxic baits with fat-soluble dye Sudan III. The dye Rhodamine-B stained the gaster in 40.31% of workers and showed no significant difference among castes. The Sudan III stained the infrabuccal cavity in 35.41%, post-pharyngeal glands of 24.22% and gaster in only 8.44% of the workers, with no significant difference among the castes. The watersoluble dye was spread in the body of workers through the digestive system while fat-soluble dye was diverted to the post-pharyngeal glands.
Keywords: digestive system; glands; leaf-cutting ants; manipulation; toxic baits